Efektivitas Pelatihan Dan Pengembangan Guru Dalam Mencapai Tujuan Pendidikan Yang Unggul - Reni Andryani; Iryanah Iryanah; Irfan Firdaus; Budi Ilham Maliki (Journal on Education, 2024)
In light of current needs for educational innovation and creativity, this study seeks to address the issue of how to better equip educators to act as agents of student learning. The study's overarching goal is to help relevant stakeholders including policymakers, educators, and school districts by providing evidence-based insights into how teacher professional development programmes affect student achievement in a high-quality education setting. Using a "census sampling" strategy, this research surveyed all 41 instructors at a single public high school; data came from in-person observations, online surveys, and multiple linear regression analysis. A favourable and statistically significant relationship between Excellent Education and the Effectiveness of Teacher Training and Development was found. However, when all of the independent variables are considered together, they account for or explain 73.9% of the variance in Excellent Education. The findings of this study should help shape national education policy and HRD initiatives aimed at raising educational standards.